1973
DOI: 10.1111/j.1365-2133.1973.tb07587.x
|View full text |Cite
|
Sign up to set email alerts
|

comparison between DNA synthesis and mitosis in uninvolved and involved psoriatic epidermis and normal epidermis

Abstract: summary Biopsies have been taken from the involved and uninvolved skin of eleven patients with psoriasis and the normal skin of six patients without psoriasis, 1 h after in vivo injection of 10 μCi of 3H‐thymidine. Mitotic counts and counts of labelled cells (synesizing DNA) after autoradiography have been carried out. The ratio of mitoses to labelled cells was 1: 25 in clinical psoriasis, 1: 190 in uninvolved psoriatic epidermis and 1: 450 in normal epidermis. The number of labelled cells in clinical psoriasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
2

Year Published

1980
1980
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 11 publications
2
27
2
Order By: Relevance
“…Although a large number of publications might lead to the conclusion that uninvolved psoriatic skin possesses several features similar to involved psoriatic skin, it is important to note that, in the literature, results about uninvolved skin are still often contradictory. For example, some studies demonstrated that cell proliferation in uninvolved psoriatic skin was similar to what was observed in involved skin (Barker et al ., ; Harper et al ., ), whereas others showed that uninvolved psoriatic cell proliferation rather mimicked normal skin (Goodwin et al ., ; Weinstein and Frost, ). Pershing et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although a large number of publications might lead to the conclusion that uninvolved psoriatic skin possesses several features similar to involved psoriatic skin, it is important to note that, in the literature, results about uninvolved skin are still often contradictory. For example, some studies demonstrated that cell proliferation in uninvolved psoriatic skin was similar to what was observed in involved skin (Barker et al ., ; Harper et al ., ), whereas others showed that uninvolved psoriatic cell proliferation rather mimicked normal skin (Goodwin et al ., ; Weinstein and Frost, ). Pershing et al .…”
Section: Introductionmentioning
confidence: 99%
“…The increased proliferation of epidermal cells is not restricted to the psoriatic lesion but has also been demonstrated in elinieMly unaffected skin (4).…”
Section: Discussionmentioning
confidence: 96%
“…In these studies Ralfs et al (1980) have demonstrated a five-fold higher rate of entry of cells into S than into mitosis. An earlier study of Goodwin, Hamilton & Fry (1973) had shown that the ratio of labelled cells: mitotic cells was 27:1 for psoriatic and 450:1 for normal epidermis. Large labelled cell: mitotic cell ratios have more recently been confirmed in normal epidermis by the more detailed studies of Cample John & Gelfant (1981).…”
mentioning
confidence: 92%